2005
DOI: 10.1074/jbc.m505568200
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of VE-cadherin Prevents Binding of p120- and β-Catenin and Maintains the Cellular Mesenchymal State

Abstract: In several pathological conditions, epithelial cells demonstrate a breakdown of barrier function and acquire an invasive phenotype. Endothelial cells in particular are maintained in a mesenchymal state during the cell invasion phase of angiogenesis. We show here that tyrosine phosphorylation of the adherens junction protein VE-cadherin at two critical tyrosines, Tyr-658 and Tyr-731, via tyrosine kinase activation or phosphatase inactivation was sufficient to prevent the binding of p120-and ␤-catenin, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
295
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 300 publications
(314 citation statements)
references
References 40 publications
15
295
2
2
Order By: Relevance
“…However, tyrosine phosphorylation is a well characterized cause of VE-cadherin junction opening and increased vascular permeability (24). Phosphorylation has been linked to both endocytosis of VE-cadherin (25) and the dissociation of VE-cadherin from ␤-catenin and subsequent loss of stable association with the cortical actin cytoskeleton (26). Because we observed ostensible internalization of VE-cadherin (Fig.…”
Section: Ascorbate Stabilizes Peripheral Actin and Cell-cell Junctionmentioning
confidence: 90%
“…However, tyrosine phosphorylation is a well characterized cause of VE-cadherin junction opening and increased vascular permeability (24). Phosphorylation has been linked to both endocytosis of VE-cadherin (25) and the dissociation of VE-cadherin from ␤-catenin and subsequent loss of stable association with the cortical actin cytoskeleton (26). Because we observed ostensible internalization of VE-cadherin (Fig.…”
Section: Ascorbate Stabilizes Peripheral Actin and Cell-cell Junctionmentioning
confidence: 90%
“…The Cheresh lab showed that VE-cadherin phosphorylation on Tyr658 or Tyr731, but not other tyrosines, was sufficient to maintain cells in a mesenchymal state ( ). More work is necessary to Potter et al 2005 understand which tyrosine is targeted in which condition.…”
Section: Tyrosine Phosphorylation Of Ve-cadherinmentioning
confidence: 99%
“…[65][66][67] Many of these functions were also demonstrated for regulation of the VE-cadherin in endothelium. [68][69][70][71][72][73][74][75][76] Importantly, recent data indicates the involvement of p120 ctn in controlling ARP2/3 complex-mediated actin polymerization at endothelial junctions, by binding to the nuclear-promoting factors Wiskott-Aldrich Syndrome Protein (N-WASP) 21 and to cortactin. 77,78 Both the ARP2/3 complex 11,21 and cortactin [79][80][81][82][83][84][85] control endothelial integrity, and particularly, N-WASP control ARP2/3 complex-mediated formation of new VE-cadherin adhesion sites, which drive the VE-cadherin dynamics.…”
Section: Impact Of α-Catenin In Linking Actin Filaments To the Ve-cadmentioning
confidence: 99%